Activated Chicken Gamma Delta T Cells Are Involved in Protective Immunity against Marek’s Disease - Ayumi Matsuyama-Kato; Bahram Shojadoost; Nitish Boodhoo; Sugandha Raj; Mohammadali Alizadeh; Fatemeh Fazel; Charlotte Fletcher; Jiayu Zheng; Bhavya Gupta; Mohamed Faizal Abdul-Careem; Brandon L. Plattner; Shahriar Behboudi; et al. (Viruses, 2023)
Gamma delta (γδ) T cells play a significant role in the prevention of viral infection and tumor surveillance in mammals. Although the involvement of γδ T cells in Marek’s disease virus (MDV) infection has been suggested, their detailed contribution to immunity against MDV or the progression of Marek’s disease (MD) remains unknown. In the current study, T cell receptor (TCR)γδ-activated peripheral blood mononuclear cells (PBMCs) were infused into recipient chickens and their effects were examined in the context of tumor formation by MDV and immunity against MDV. We demonstrated that the adoptive transfer of TCRγδ-activated PBMCs reduced virus replication in the lungs and tumor incidence in MDV-challenged chickens. Infusion of TCRγδ-activated PBMCs induced IFN-γ-producing γδ T cells at 10 days post-infection (dpi), and degranulation activity in circulating γδ T cell and CD8α+ γδ T cells at 10 and 21 dpi in MDV-challenged chickens. Additionally, the upregulation of IFN-γ and granzyme A gene expression at 10 dpi was significant in the spleen of the TCRγδ-activated PBMCs-infused and MDV-challenged group compared to the control group. Taken together, our results revealed that TCRγδ stimulation promotes the effector function of chicken γδ T cells, and these effector γδ T cells may be involved in protection against MD.